Penguatan Berkebhinekaan Global dalam Profil Pelajar Pancasila Melalui Bahasa Inggris (Persepsi Mahasiswa) - Neneng Rika Jazilatul Kholidah; Chyntia Heru Woro Prastiwi; Fifi Zuhriah; Siswanti Ika Yulianti; Muhammad Ibrohim (IKIP PGRI Bojonegoro, 2023)
Abstract : The Pancasila student profile is a translation of Indonesia's national education goals to build the character and competence of students. Global diversity is one dimension of the Pancasila student profile. This dimension has four elements and 11 sub-elements. In elements 1) knowing and appreciating the culture and 2) communication and interaction between cultures, English plays an important role because these two elements contain a global or international context. By applying a mixed method and taking as many as 100 research subjects from three study programs (PPKn, Economics Education, and English Language Education) at a private university in Bojonegoro Regency in November 2022, this study aims to investigate students' perceptions of the role of English for strengthening global diversity in the profiles of Pancasila students. Data on the students’ perceptions were collected by distributing questionnaires and conducting interviews. Students' positive perceptions of English will accelerate the competency achievement of Pancasila student profiles on the global diversity dimension. The results of the study indicated that students have positive and negative perceptions of English. However, they have a positive perception of the role of English in strengthening the global diversity dimension in the profiles of Pancasila students. University plays vital roles in developing the positive students’ perceptions. Keywords: Pancasila student profile, global diversity, student’s perception Abstrak: Profil pelajar Pancasila merupakan bentuk penerjemahan tujuan pendidikan nasional Indonesia untuk membangun karakter serta kompetensi peserta didik. Berkebhinekaan global adalah salah satu dimensi pada profil pelajar Pancasila. Dimensi ini memiliki 4 elemen dan 11 sub-elemen. Pada elemen 1) mengenal dan menghargai budaya dan 2) komunikasi dan interaksi antar budaya, bahasa Inggris memegang peranan penting karena kedua elemen ini mengandung konteks global/internasional. Dengan menerapkan mixed method dan mengambil subyek penelitian sebanyak 100 mahasiswa dari 3 program studi (PPKn, Pendidikan Ekonomi, dan Pendidikan Bahasa Inggris) di sebuah universitas swasta di Kabupaten Bojonegoro pada bulan November 2022, penelitian ini bertujuan menginvestigasi persepsi mahasiswa tentang peran bahasa Inggris untuk penguatan kebhinekaan global dalam profil pelajar Pancasila. Data persepsi mahasiswa diperoleh dengan cara menyebarkan kuisioner dan melakukan interview. Persepsi positif mahasiswa terhadap bahasa Inggris akan mengakselerasi capaian kompetensi profil pelajar Pancasila pada dimensi berkebhinekaan global. Hasil penelitian menunjukkan bahwa mahasiswa memiliki persepsi positif dan negative terhadap bahasa Inggris. Akan tetapi, mereka memiliki persepsi positif pada peran bahasa Inggris untuk memperkuat dimensi berkebhinekaan global pada profil pelajar Pancasila. Perguruan tinggi memegang peran penting untuk membentuk persepsi positif mahasiswa. Kata kunci: profil pelajar Pancasila, berkebhinekaan global, persepsi mahasiswa